The endometrium in assisted reproductive technology: How thin is thin? - Nalini Mahajan; S Sharma (Wolters Kluwer Medknow Publications, 2016)
A thin endometrium is encountered infrequently (2.4%) in assisted reproductive technology cycles. When it does occur it is a cause of concern as it is associated with lower implantation rate and pregnancy rate. Though pregnancies have been reported at 4 and 5 mm it is apparent that an endometrial thickness <6 mm is associated with a trend toward lower probability of pregnancy. Hormone replacement therapy - frozen embryo transfer (FET) cycles appear to give better results due to an improvement in endometrial receptivity (ER). The etiology of thin endometrium plays a significant part in its receptivity. A number of treatments have been tried to improve endometrial growth, but none has been validated so far. Confirming ER of a thin endometrium by an ER array test before FET offers reassurance.